Assessment of the carbonized woody briquette gasification in an updraft fixed bed gasifier using the Euler-Euler model. (15th June 2018) - Lu, Ding; Yoshikawa, Kunio; Ismail, Tamer M.; Abd El-Salam, M.
Graphical abstract: Highlights: The first study on carbonized briquette gasification by both simulation and experiment. Effects of ER, and particle size were well evaluated by simulation. Carbonized briquette can be well utilized for the low tar production issues. Abstract: This paper reports on the numerical simulation and experimental studies of carbonized woody briquettes gasification employing an updraft fixed bed gasifier. There is a strong industrial stake when it comes to the optimization of this gasification process, in terms of the flexibility of the type of biomass and its conversion efficiency. The influences of the gasification temperature and the equivalence ratio (ER) on the gaseous production and the tar yield were examined. In order to optimize the operating conditions of the biomass gasification process, a numerical model was developed using the COMMENT code (Combustion Mathematics and Energy Transport). This model is a two-dimensional computer model describing the biomass gasification process in an updraft gasifier using carbonized woody briquettes as fuel. The present study proved that ER significantly influenced the composition of gaseous species and its optimization is important to obtain a higher gasification rate. The particle size presented considerable effects on the temperature distribution within the gasifier and the syngas compositions produced during the gasification process as well. The numerical model presented was validated by the experimental results and it provided a promising way to simulate the gasification of solid fuel, which is considered to be a versatile and useful computational tool to optimize the biomass gasification process and to design fixed bed gasifiers.